Economic Empowerment of Coffee Farmers Through Dompet Dhuafa’s Social Enterprise Program - Umaima; Muh. Yusuf; Mukhtar Yunus; Muhammad Jabbarul Qubra (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
The empowerment of coffee farmer groups by Dompet Dhuafa aims to improve the welfare and income of farmers in Letta Village, Lembang District, Pinrang Regency through a social enterprise program. This research uses a descriptive qualitative method to explore field facts related to the implementation of the program. The results show the pattern of implementing a social enterprise program that prioritizes elements such as social values, civil society, innovation, and economic activity. Dompet Dhuafa provides a coffee roaster machine for the business partner, warkop Gudmud, with funding from ZISWAF, and the profits obtained are used to provide sustainable social impact for the community.